Echocardiography for latent rheumatic heart disease in first degree relatives of children with acute rheumatic fever: Implications for active case finding in family members. (July 2021) - Culliford-Semmens, Nicola; Tilton, Elizabeth; Wilson, Nigel; Stirling, John; Doughty, Robert; Gentles, Thomas; Peat, Briar; Dimalapang, Eliazar; Webb, Rachel
Abstract: Background: Individuals with Acute Rheumatic Fever (ARF) often report a family history of ARF or Rheumatic Heart Disease (RHD) however the degree of familial susceptibility to RHD is poorly defined. This study aimed to determine RHD prevalence among first degree relatives of ARF patients using echocardiography. Methods: Children with ARF were recruited from Auckland, New Zealand. Parents and siblings ≥ 4years were offered echocardiography. Echocardiograms were reported according to World Heart Federation 2012 criteria. RHD prevalence in first degree relatives was compared to previously established population rates in the region. Findings: In total, 70 index cases with ARF were recruited. Echocardiography was performed in 94 parents and 132 siblings. There were 3 siblings with definite RHD and 9 with borderline RHD. There were 4 parents with definite RHD. Overall prevalence of RHD (definite and borderline) in siblings was 90/1, 000 (95% CI 45–143/1, 000) compared to 36/1, 000 (95% CI 30–42/1, 000) in New Zealand children from high ARF incidence populations (p 0.001). Prevalence of definite RHD in parents was 42/1, 000 (95% CI 7–87/1, 000) compared to 22/1, 000 (95% CI 9–36/1, 000) in adults from a high ARF incidence New Zealand population (p 0.249). Interpretation: RHD prevalence in siblings and parents of ARF cases is significantly greater than in comparable background populations. The contribution of hereditary versus environmental risk factors remains uncertain. We recommend targeted echocardiographic case-finding among siblings and parents of ARF/RHD cases in order to detect previously unrecognized latent RHD.